1996
DOI: 10.1002/(sici)1096-8644(199605)100:1<89::aid-ajpa9>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the pelvic midplane and its relationship to Neandertal reproductive patterns

Abstract: The fragmentary nature of the fossil record has limited the analysis of the Neandertal pelvis to the superior pubic ramus and the pelvic inlet. From an obstetric viewpoint, the pelvic midplane or "plane of least dimensions," defined by the distance between the ischial spines, must be considered in the analysis of hominid reproduction. We examined the relationship between BSD and weight in a mixed sex hospital population undergoing diagnostic computed tomography (CT) scans (41 females and 40 males). Because fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…The measures of the midplane area have significant negative partial correlation with femoral length [13]. In addition, the bispinous diameter has no correlation with height [11,16]. Therefore, the females with a shorter stature can have a wider pelvic midplane and on the contrary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measures of the midplane area have significant negative partial correlation with femoral length [13]. In addition, the bispinous diameter has no correlation with height [11,16]. Therefore, the females with a shorter stature can have a wider pelvic midplane and on the contrary.…”
Section: Discussionmentioning
confidence: 99%
“…The obstetric importance of the pelvic inlet and the midplane was emphasized in anthropological studies [3,4,16,17]. In a typical female pelvis, a longer diameter of the inlet (the transverse diameter) and a longer diameter of the midplane (the anteroposterior diameter) are placed perpendicularly.…”
mentioning
confidence: 99%
“…Specifically, these differences seem important in the transverse diameter of the mid-plane or bi-spinous (Correia et al, 2005;Kurki, 2005Kurki, , 2007 which is a constant in both types of studies. Perhaps, the mid-plane is a critical obstetric plane (Correia et al, 2005;Oxorn, 1986;Walrath and Glantz, 1996;Zaretsky et al, 2005) because it is located at the level of the ischial spines, which may constrict the birth canal (Oxorn, 1986;Walrath and Glantz, 1996;Zaretsky et al, 2005). Specifically, the sexual dimorphism of the transverse diameter of the mid-plane could be explained by the rotative mechanism of human parturition, and the possible bi-parietal deformation of the baby's cranium during labour (Borell and Fernström, 1958a,b).…”
Section: Discussionmentioning
confidence: 99%
“…All of this variation makes the characterisation of a single or standard mechanism of childbirth difficult, in terms of a standard orientation of the foetus as it passes through the canal. Although rotation of the foetus is a consistent feature, foetal orientation at each canal plane is dependent on canal geometry (Walrath and Glantz, 1996). The high degree of "evolvability" (evolutionary variability) in human pelves as demonstrated Grabowski (2013) has enabled the generation of diverse pelvic geometries among and within human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Walrath and Glanz described sexual dimorphism in the predictors of the bispinous diameter and found that the body weight and the femoral head diameter squared are the predictors of the diameter only in females [18], while Tague has not found sexual dimorphism in the described relationship [17]. At the same time, Walrath and Glanz found that the transverse diameter of the inlet is a predictor of the bispinous diameter in both sexes [18]. Th e present study confi rmed sexual dimorphism in the predictors of the narrowest pelvic diameter in the sense of the explained variance and of the number of predictors.…”
Section: Discussionmentioning
confidence: 99%